Video-based Learning for Knowledge and Readiness on Waste Separation at Source (WSAS) Practice among Engineering Students - Sitty Nur Syafa Bakri (PT. Pusmedia Group Indonesia, 2024)
Video-based learning is a visual storytelling that have proven to be highly effective tools in disseminating information and engaging students. In this study, waste separation at source (WSAS) were demonstrated in a video to explores the effectiveness of video-based learning in promoting knowledge and readiness for WSAS practice among engineering students. The students were exposed to two types of videos: Video 1-Penang and Video 2-Sapporo. After watching both videos, they were given a questionnaire to assess their willingness to practice WSAS and the level of knowledge gained on the subject. The finding indicated that students answered higher percentages (scale 4-5) for knowledge learned through video visualisation. All students agreed to do WSAS with correlation of 0.7 between their knowledge gained and willingness to adopt the practice. For immediate action for waste separation implementation, 85% of the students prefer to adopt Video 1-Penang over Video 2-Sapporo. Therefore, this study suggests that utilisation of video-based learning in educating engineering students has proven to be effective in promoting knowledge and readiness about waste separation at source practice. Based on the results of the study, the implications that can be identified are that video-based learning has proven to be effective as an educational tool to improve students' knowledge and readiness in the practice of waste sorting at source (WSAS)